Dampak Pengelolaan Kelas terhadap Perkembangan Sosial Emosional Anak Usia Dini di TK Lab. STAI YPBWI Surabaya - Sutiyah Nova Irawati (Universitas Islam Lamongan, 2025)
Early childhood development can be influenced by the learning atmosphere in the classroom. Therefore, classroom management is very important to create an effective classroom atmosphere and conditions in supporting the development of social-emotional development of early childhood students. This study aims to describe the application of classroom management in TK Lab. STAI YPBWI Surabaya. This descriptive qualitative research involved the principal and class teachers as research subjects. Data were collected through observation, interviews, and document analysis. Qualitative data analysis was carried out with the stages of data reduction, data display, and drawing conclusions. The research findings show that: 1) classroom management in TK Lab. STAI YPBWI Surabaya includes: a) physical arrangement and classroom environment, b) management of time and study schedule, c) use of personal affective approach in teacher and student interaction, d) Involvement of children in classroom management; 2) the impact of classroom management on social emotional development is seen in the progress of children's ability to interact positively, such as sharing play equipment, waiting for their turn, apologizing, and helping friends who are having difficulties. In addition, children appear more open in expressing their feelings, both to teachers and peers, and are able to recognize and name basic emotions such as happy, angry, sad, and afraid. Through the involvement of children in classroom management, children learn about self-discipline, can foster habits of responsible attitudes, in problem solving and decision making.